Evolution of the Content of the Market Category at Different Stages of its Development - Saubanov, Kabir; Nikolaev, Mikhail (Journal of History Culture and Art Research, 2018)
The “market” concept is one of the key concepts of modern economic theory, as well aseconomic practice. It plays an exceptional role in understanding and explaining the properties and patterns ofbehavior of not only individual economic agents, but also economic systems in general. At the same time, up to the present time there is no unified, unconditionally accepted by all researchers definition of the market category, there are about two hundred of which. Such a multitude of definitions, most of which have anarrowly specific, partial character and are applicable only for individual cases, attests in the first place to the extremely high complexity and ambiguity of the content of the market category, as well as its large information capacity. Allthiscertainly speaks about the relevance of the chosen research topic. The essence and content of the market concept at various stages of economic evolution are analyzed in the paper; author’s interpretation of theessence of the market and the main components of its content is offered. Among these components, the mostimportantare the freedom of entrepreneurship, competition and market infrastructure, the individual elements of which are usually identified with the market. The authors analyze the subordination of market elements and their interactionand show that many other market elements (the next order) can be logically derived from the main constituents of the content, resulting from both their interaction with each other and the response to their interaction with the continuously developing external environment.